METASTASIS OF BREAST CANCER IN THE OVARIES. SURVIVAL AND PROGNOSTIC FACTORS - S. N. Tadzhibov; S. B. Polikarpova; T. M. Kochoyan; N. I. Mehtieva; R. A. Kerimov; A. I. Berishvili (ABV-press, 2017)
Introduction. In 70 % of patients with metastases of breast cancer in the ovaries, ovarian damage is detected simultaneously with the primary tumor, which affects the choice of tactics for diagnosis and treatment of such patients.Materials and methods. The data of 30 patients with breast cancer with ovarian metastases and 35 patients with breast cancer without metastatic ovarian damage, which comprised the main and control groups. The groups were comparable in terms of main demographic and clinical features. Results. In the study of distant indicators, it is proved that the presence of metastases in the ovaries is a reliable adverse factor predicting a 3-year overall survival of patients older than 50 years who are in menopause and who received combined treatment.Conclusions. Surgical treatment significantly increases the 3and 5-year overall survival of breast cancer patients with ovarian metastases (83.3 %), while the combined treatment of such patients does not significantly affect overall survival despite the high sensitivity of breast cancer to chemotherapy. This may be due to the fact that the patients included in the study who received the combined treatment had metastases to other organs (liver, lungs, bones).